Prevalence and consequences of Ewu-ukwu custom in Mbaise, Imo State, Nigeria (2008)
Studies have consistently shown that fertility among the Igbo of Southeast Nigeria is high, and particularly higher among the Mbaise people. Multiple socio-economic and cultural factors such as son preference, stigma and discrimination ascribed to childlessness and other relevant practices in different communities bolster frequent child-bearing among Igbo women even without prompting from their husbands and, at times in conditions that threaten their lives. In Mbaise in particular, the ewu-ukwu custom which is celebrated to honour a woman after her tenth child is perceived as an index of accomplishment and self-actualization. The objectives of the study are to examine the prevalence of the ewu-ukwu custom in Mbaise, and to identify the categories of people who are breaking with the tradition by discontinuing the practice and the factors motivating them to do so. Furthermore, the consequences of the custom on maternal and child health as well as on care and welfare of young people was explored. The findings indicate that the custom has waned, but as long as it lasted, the quest for induction into this relatively privileged social group shored up high fertility, and is associated with high maternal and infant mortality and morbidity which are themselves exacerbated by poor health facilities. Also, the ewu-ukwu custom has multidimensional implications for the wellbeing and gender roles of relevant individuals and groups which call for urgent interventions and societal re-orientation